2019
DOI: 10.1002/cpe.5107
|View full text |Cite
|
Sign up to set email alerts
|

Systematic literature review of sentiment analysis on Twitter using soft computing techniques

Abstract: Sentiment detection and classification is the latest fad for social analytics on Web. With the array of practical applications in healthcare, finance, media, consumer markets, and government, distilling the voice of public to gain insight to target information and reviews is non-trivial. With a marked increase in the size, subjectivity, and diversity of social web-data, the vagueness, uncertainty and imprecision within the information has increased manifold. Soft computing techniques have been used to handle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(64 citation statements)
references
References 80 publications
(208 reference statements)
0
62
0
2
Order By: Relevance
“…Opinion polarity takes into account the amount of positive or negative terms that appear in a given text (Kumar & Sebastian, 2012a;Kumar & Sebastian, 2012b;2012c, Kumar et al 2015Kumar & Joshi, 2017a;Kumar & Joshi, 2017b;Kumar & Jaiswal, 2017;Kumar & Khorwal, 2017;Kumar & Sharma, 2017;Son et al, 2019;Kumar & Jaiswal, 2019;Kumar & Garg, 2019). In this research, to determine the polarity of tweets, SentiWordNet is used.…”
Section: Negative Polarity Tweetsmentioning
confidence: 99%
“…Opinion polarity takes into account the amount of positive or negative terms that appear in a given text (Kumar & Sebastian, 2012a;Kumar & Sebastian, 2012b;2012c, Kumar et al 2015Kumar & Joshi, 2017a;Kumar & Joshi, 2017b;Kumar & Jaiswal, 2017;Kumar & Khorwal, 2017;Kumar & Sharma, 2017;Son et al, 2019;Kumar & Jaiswal, 2019;Kumar & Garg, 2019). In this research, to determine the polarity of tweets, SentiWordNet is used.…”
Section: Negative Polarity Tweetsmentioning
confidence: 99%
“…It has gradually emerged as a huge source of sentiment-rich data [4]. The keyword ''sentiment analysis'' was initially witnessed in the published work [5] in 2003, and since then, both primary [4], [6], [7] and secondary studies have been reported across pertinent literature [8]- [11]. Furthermore, the literature is well-equipped with studies pertaining to sentiment analysis using machine learning paradigms on specifically textual user-generated online content on social media.…”
Section: Related Workmentioning
confidence: 99%
“…The output is thus a weighted combination of all the input states, not just the last state. The attention mechanism gives an attention score e i,t to each word t in the sentence i, as given by (11).…”
Section: ) Attention Layermentioning
confidence: 99%
“…Kumar and Jaiswal presented a systematic literature review to collate, explore, understand, and analyze the efforts and trends in a well‐structured manner to identify research gaps defining the future prospects of this coupling. The contribution of this paper is significant because firstly the primary focus is to study and evaluate the use of soft computing techniques for sentiment analysis on Twitter, and secondly, as compared to the previous reviews, we adopt a systematic approach to identify and gather empirical evidence, interpret results, and critically analyze and integrate the findings of all relevant high‐quality studies to address specific research questions pertaining to the defined research domain.…”
Section: Theme Of This Special Issuementioning
confidence: 99%